CONTROL OF SPECIFIC GENE EXPRESSION EXAMINED IN SYNCHRONIZED MAMMALIAN CELLS - Martin, David W. (1969)
The control of synthesis of the steroid-inducible enzyme, tyrosine aminotransferase (TAT), has been studied in synchronized cultures of HTC cells, an established line of rat hepatoma cells. During the mitotic and early G1 periods of the generation cycle of cells previously exposed to inducer, TAT synthesis is maximal in the absence of inducer, i.e., synthesis is constitutive. (By contrast, in random cells maximal TAT synthesis is always dependent upon the presence of the inducer.) After the third hour of G1 “G1[3]”), TAT synthesis is inhibited by a specific posttranscriptional repressor, the formation of which requires RNA synthesis. We speculate that this repressor is antagonized by the steroid inducer. The degradation of TAT during mitosis and G1 is constant and not affected by cycloheximide or actinomycin D in our experiments.